Telomere Dysfunction in Oocytes and Embryos From Obese Mice - Ge, Juan; Li, Congyang; Sun, Hongzheng; Xin, Yongan; Zhu, Shuai; Liu, Yuan; Tang, Shoubin; Han, Longsen; Huang, Zhenyue; Wang, Qiang (Frontiers in Cell and Developmental Biology, 2021)
Maternal obesity impairs oocyte quality and embryo development. However, the potential molecular pathways remain to be explored. In the present study, using mice fed a high-fat diet (HFD) as a model, we examined the effects of obesity on telomere status in oocytes and embryos. Of note, telomere shortening was observed in both oocytes and early embryos from obese mice, as evidenced by the reduced expression of telomerase reverse transcriptase (TERT) and activity of telomerase. Moreover, quantitative analysis of telomere dysfunction-induced foci (TIFs) revealed that maternal obesity induces the defective telomeres in oocytes and embryos. Meanwhile, the high frequency of aneuploidy was detected in HFD oocytes and embryos as compared to controls, accompanying with the increased incidence of apoptotic blastocysts. In conclusion, telomere dysfunction may represent a critical mechanism mediating the effects of maternal obesity on oocyte quality and embryo development.